Report on a computer-controlled automatic test platform for precision RF cavity characterizations. (26th November 2015) - Chen, X; Sanjari, M S; Piotrowski, J; Hülsmann, P; Litvinov, Yu A; Nolden, F; Steck, M; Stöhlker, Th
Abstract: An automated test platform aiming at accurate and efficient cavity characterizations has recently been set up at GSI, Darmstadt. In this proceeding the composition of such a system, on both hardware and software sides, is described in detail. The amount of necessary human work is significantly reduced to the minimum, while the measurement precision is improved considerably.